Pathophysiology of sepsis-induced cardiomyopathy - Hollenberg, Steven M; Singer, Mervyn (Nature reviews cardiology, 2021)
Sepsis is the life-threatening organ dysfunction caused by a dysregulated host response to infection and is the leading cause of death in intensive care units. Cardiac dysfunction caused by sepsis, usually termed sepsis-induced cardiomyopathy, is common and has long been a subject of interest. In this Review, we explore the definition, epidemiology, diagnosis and pathophysiology of septic cardiomyopathy, with an emphasis on how best to interpret this condition in the clinical context. Advances in diagnostic techniques have increased the sensitivity of detection of myocardial abnormalities but have posed challenges in linking those abnormalities to therapeutic strategies and relevant clinical outcomes. Sophisticated methodologies have elucidated various pathophysiological mechanisms but the extent to which these are adaptive responses is yet to be definitively answered. Although the indications for monitoring and treating septic cardiomyopathy are clinical and directed towards restoring tissue perfusion, a better understanding of the course and implications of septic cardiomyopathy can help to optimize interventions and improve clinical outcomes.